A nanofoaming process and dielectric properties of polymethylphenylsilsesquioxane-based nanofoams - Hong, SM; Hwang, SS (WILEY, 2006)
We prepared polymethylphenylsilsesequioxane (PMPSQ) as an inorganic, thermally stable, matrix and poly-D,L-lactide-1,6-hexanediol (PDLLA-1,6-hexanediol) as a porogen material. PMPSQ was initially designed to obtain synergistic effects from polyphenylsilsesquioxane and polymethylsilsesquioxane. The PDLLA-1,6-hexanediol was chosen as a porogen since it has a much lower thermal stability when compared with PMPSQ. The initial decomposition temperature of the PMPSQ (458 degrees C) was higher than the terminal decomposition temperature of PDLLA-1,6-hexanediol by 148 degrees C, resulting in a broad processing window for the nanofoaming process. The broad window was utilized not only for optimization of the foaming condition, but for preparation of the nanofoamed PMPSQ without disruption in the structural stability of the matrix. Furthermore, hydroxyl end groups on PMPSQ and PDLLA-1,6-hexanediol played a role in the uniform and well-distributed phase separation behavior. PMPSQ and PDLLA-1,6-hexanediol were investigated by H-1 NMR, GPC, and thermogravimetric analysis to characterize the properties of polymers and optimize the foaming condition. The inorganic/organic hybrids based on the PMPSQ and PDLLA-1,6-hexanediol were prepared and measured in terms of phase separation behavior and dielectric properties. In these hybrid systems, PMPSQ/PDLLA-1,6-hexanediol (85/15) exhibited the most uniform and the smallest nanofoam distribution in the continuous PMPSQ matrix. (c) 2006 Wiley Periodicals, Inc.
Keywords: CONSTANT; POLY(PHENYLSILSESQUIOXANE); POLYCONDENSATION; POLYMERS; FILMS